Multilocus Sequence Analysis of Cercospora spp. from Different Host Plant Families - Yuliarni, Floreta Fiska; Sjamsuridzal, Wellyzar; Hidayat, Iman (UI Scholars Hub, 2013)
Identification of the genus Cercospora is still complicated due to the host preferences often being used as the main criteria to propose a new name. We determined the relationship between host plants and multilocus sequence variations (ITS rDNA including 5.8S rDNA, elongation factor 1-α, and calmodulin) in Cercospora spp. to investigate the host specificity. We used 53 strains of Cercospora spp. infecting 12 plant families for phylogenetic analysis. The sequences of 23 strains of Cercospora spp. infecting the plant families of Asteraceae, Cucurbitaceae, and Solanaceae were determined in this study. The sequences of 30 strains of Cercospora spp. infecting the plant families of Fabaceae, Amaranthaceae, Apiaceae, Plumbaginaceae, Malvaceae, Cistaceae, Plantaginaceae, Lamiaceae, and Poaceae were obtained from GenBank. The molecular phylogenetic analysis revealed that the majority of Cercospora species lack host specificity, and only C. zinniicola, C. zeina, C. zeae-maydis, C. cocciniae, and C. mikaniicola were found to be host-specific. Closely related species of Cercospora could not be distinguished using molecular analyses of ITS, EF, and CAL gene regions. The topology of the phylogenetic tree based on the CAL gene showed a better topology and Cercospora species separation than the trees developed based on the ITS rDNA region or the EF gene.